The Role of Religiosity in Happiness of Vocational School Students in Indonesia - Putri Dwi Lestari; Effy Wardati Maryam (Universitas Muhammadiyah Sidoarjo, 2020)
This research is quantitative research with a correlational approach. This study aims to determine the relationship between religious and happiness in students class XII SMK 10 Nopember Sidoarjo. This research was conducted at SMK 10 Nopember Sidoarjo with a sample of 220 students who were selected using the cluster random sampling technique. Data collection technique in this study used two psychologycalscales with Likert models, namely the scale of religious and happiness. The hypothesis in this study is that there is a positive relationship between religious and happiness in SMK 10 Nopember Sidoarjo. Data analysis was carried out with Spearman Rank correlation technique using SPSS 22.0 for Windows program. The results of the data analysis showed a correlation coefficient of 0.863 with significance of 0.000 < 0.05. this means that is a positive relationship between religious with happiness.